2009
DOI: 10.4049/jimmunol.0803654
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Reduction of Functionally Suppressive CD4dimCD25highFoxp3+ Tregs in Human Second Trimester Pregnancy Is Induced by Progesterone and 17β-Estradiol

Abstract: CD4+CD25high regulatory T cells (Tregs) are implicated in the maintenance of murine pregnancy. However, reports regarding circulating Treg frequencies in human pregnancy are inconsistent, and the functionality and phenotype of these cells in pregnancy have not been clarified. The aim of this study was to determine the frequency, phenotype, and function of circulating Tregs in the second trimester of human pregnancy and the influence of progesterone and 17β-estradiol on Treg phenotype and frequency. Based on ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 53 publications
(50 reference statements)
6
81
3
1
Order By: Relevance
“…In a recent study, where a more definitive phenotyping strategy was used, it was found that CD4 + CD25 + CD127 lo FoxP3 + T-cells were reduced in the second trimester and that expression of FoxP3 itself was lower with pregnancy. The function of this population in pregnant women was comparable to that in non-pregnant women (45) . CD4 + CD25 + T-cells are relatively abundant in first trimester decidua (about 20 % of decidual CD4 + T-cells v. about 8 % of CD4 + T-cells in peripheral blood of pregnant Proceedings of the Nutrition Society women) and they respond poorly to T-cell stimulation and have suppressive activity that is cell-contact dependent (46) .…”
Section: Regulatory T-cellsmentioning
confidence: 51%
See 1 more Smart Citation
“…In a recent study, where a more definitive phenotyping strategy was used, it was found that CD4 + CD25 + CD127 lo FoxP3 + T-cells were reduced in the second trimester and that expression of FoxP3 itself was lower with pregnancy. The function of this population in pregnant women was comparable to that in non-pregnant women (45) . CD4 + CD25 + T-cells are relatively abundant in first trimester decidua (about 20 % of decidual CD4 + T-cells v. about 8 % of CD4 + T-cells in peripheral blood of pregnant Proceedings of the Nutrition Society women) and they respond poorly to T-cell stimulation and have suppressive activity that is cell-contact dependent (46) .…”
Section: Regulatory T-cellsmentioning
confidence: 51%
“…Therefore, it has been suggested that the expansion in these cells is not driven by exposure to fetal alloantigen. This has led to interest in the impact of pregnancy-related hormones on these cells and both estradiol and progesterone have been implicated (45,47) . However, in another animal study, CD4 + CD25 + T-regulatory cell numbers were greater in allogeneic v. syngeneic pregnancies with the number of male offspring in the litter having a positive impact on numbers of these cells suggesting a role for fetal alloantigens (48) .…”
Section: Regulatory T-cellsmentioning
confidence: 99%
“…Progesterone has many functions that include immunosuppression, interaction with the fetal adrenals, and relaxation of the myometrium. In the placenta, progesterone initiates linkage of the Ca þþ donating protein S100 and annexin II thus activating immune relevant functions (Junqueira, Carneiro, and Kelley 2002;Lüllmann-Rauch 2003;Mjosberg et al 2009). …”
Section: Fetal Tolerance Mechanismsmentioning
confidence: 99%
“…Studies have shown an association between changes in estrogen and progesterone levels with shifts in the regulation of immune cells (Pazos, Sperling, Moran, & Kraus, 2012). For T helper cells, the number of CD4+ cells tended to increase while CD4+Foxp3+ T regulatory cell number decreased systemically during the 2 nd and 3 rd trimesters of pregnancy (Mjosberg et al, 2009;Raber-Durlacher, Leene, Palmer-Bouva, Raber, & Abraham-Inpijn, 1993). Changes in the number of CD4+ T cells coincided with reports of increased numbers of subgingival micro-organisms and increasing gingival inflammation as pregnancy progressed into the 2 nd and 3 rd trimester (Laine, 2002a;Wu et al, 2015).…”
Section: Periodontal Disease During Pregnancymentioning
confidence: 99%
“…Levels of circulating FoxP3+ Treg cells have been observed to vary at different points during pregnancy with an initial increase in the 1st trimester followed by a decrease in the 2nd trimester (Mjosberg et al, 2009). Decrease in circulating Treg cells coincides with observed onset of gingival inflammation in pregnant women (Laine, 2002a;Wu et al, 2015).…”
Section: Lower Percentage Of Treg Cells In Cd4+ T Cell Population In mentioning
confidence: 99%